2002
DOI: 10.1046/j.0014-2956.2002.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glucose transporter‐2, glucokinase and mitochondrial glycerolphosphate dehydrogenase in pancreatic islets during rat ontogenesis

Abstract: To gain better insight into the insulin secretory activity of fetal b cells in response to glucose, the expression of glucose transporter 2 (GLUT-2), glucokinase and mitochondrial glycerol phosphate dehydrogenase (mGDH) were studied. Expression of GLUT-2 mRNA and protein in pancreatic islets and liver was signi®cantly lower in fetal and suckling rats than in adult rats. The glucokinase content of fetal islets was signi®cantly higher than of suckling and adult rats, and in liver the enzyme appeared for the ®rst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(45 reference statements)
3
13
0
Order By: Relevance
“…It has been previously shown that Glut2 messages are increased in adult islets compared with those in the postnatal young mice [34,35]; here we confirmed this finding showing higher gene expression of Glut2 in adult compared to P5 and P8 islets (Fig. 6B).…”
supporting
confidence: 81%
“…It has been previously shown that Glut2 messages are increased in adult islets compared with those in the postnatal young mice [34,35]; here we confirmed this finding showing higher gene expression of Glut2 in adult compared to P5 and P8 islets (Fig. 6B).…”
supporting
confidence: 81%
“…This could be due to a number of factors. A good possibility is the lack of sufficient glucose transporters (GLUT2), as has been previously observed (11,13). As shown in Fig.…”
Section: Resultsmentioning
confidence: 66%
“…GLUT2 mRNA expression was low in islets isolated from fetal or neonatal rats, but increased to adult levels during the suckling period, whereas GLUT2 protein levels remained low until adulthood [10,11]. GCK mRNA was already at adult levels by late fetal life [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…GLUT2 mRNA expression was low in islets isolated from fetal or neonatal rats, but increased to adult levels during the suckling period, whereas GLUT2 protein levels remained low until adulthood [10,11]. GCK mRNA was already at adult levels by late fetal life [10,11]. In an immunohistochemical study, GLUT2 was restricted to pancreatic epithelium at early stages of rat fetal development and few beta cells were positive for GLUT2 until gestational day 17 [12].…”
Section: Discussionmentioning
confidence: 99%